1. Rozwiaż równania i wykonaj sprawdzenia.
a) 2(x + 1)=4
b) 4= 2(x-1)
c) 3( x-2)= x
d) 3(2x + 3)= x-1
e) 4( x-1)= 3(x + 1)
f) -(x-1) = 2
g) x=1-3(x + 1)
h) (x +1)-(x-1)=1
i) ½(x-1)=4
j) -¼(2 + x)= ¾x
k) -2(x + ½)-3(x + ⅓)=0
l) (x +2) *6= 0,5x
m) 0,1(x+2)= 0,2x
n) 6(1-⅓x)= 2(1 + ½x)
o) 0,3x - 2(0,1x +1)=0
p) 0,5(x-3) + 0,25(2x +6)=5

1

Odpowiedzi

2010-04-18T00:06:18+02:00
A)
2(x + 1)=4
2x+2=4
2x=4-2
2x=2
x=1

spr:
2(1+1)=4
2+2=4
4=4

b)
4= 2(x-1)
4=2x-2
-2x=-2-4
-2x=-6
x=3

spr:
4=2(3-1)
4=6-2
4=4

c)
3( x-2)= x
3x-6=x
3x-x=6
2x=6
x=3

spr:
3(3-2)=3
9-6=3
3=3

d)
3(2x + 3)= x-1
6x+9=x-1
6x-x=-1-9
5x=-10
x=-2

spr:
3(2*(-2)+3)=-2-1
-12+9=-3
-3=-3

e)
4( x-1)= 3(x + 1)
4x-1=3x+3
4x-3x=3+1
x=4

spr:
4*4-1=3*4+3
16-1=12+3
15=15

f) -(x-1) = 2
-x+1=2
-x=2-1
-x=1
x=-1

spr:
-(-1)+1=2
1+1=2
2=2

g)
x=1-3(x + 1)
x=1-3x-3
x+3x=1-3
4x=-2
x=-0,5

spr:
-0,5=1-3*(-0,5)-3
-0,5=1+1,5-3
-0,5=-0,5

h)
(x +1)-(x-1)=1
x+1-x+1=1
x-x=1-1-1
0≠-1

i)
½(x-1)=4
½x-½=4
½x=4+½
½x=4½
x=9

spr:
½*9-½=4
4,5-½=4
4=4

j)
-¼(2 + x)= ¾x
-½-¼x=¾x
-¼x-¾x=½
-x=½
x=-½

spr:
-½-¼*(-½)=¾*(-½)
-½+⅛=-⅜
-⅜=-⅜


k)
-2(x + ½)-3(x + ⅓)=0
-2x-1-3x-1=0
-2x-3x=1+1
-5x=2
x=-0,4

spr:
-2*(-0,4)-1-3*(-0,4)-1=0
0,8-1+1,2-1=0
0=0


l)
(x +2) *6= 0,5x
6x+12=0,5x
6x-0,5x=-12
5,5x=-12
x=-2²/₁₁

spr:
6*(-2²/₁₁)+12=0,5*(-2²/₁₁)
-13¹/₁₁+12=-1¹/₁₁
-1¹/₁₁=-1¹/₁₁


m)
0,1(x+2)= 0,2x
0,1x+0,2=0,2x
0,1x-0,2x=-0,2
-0,1x=-0,2
x=2

spr:
0,1*2+0,2=0,2*2
0,2+0,2=0,4
0,4=0,4

n)
6(1-⅓x)= 2(1 + ½x)
6-2x=2+x
-2x-x=2-6
-3x=-4
x=1⅓

spr:
6-2*1⅓=2+1⅓
6-2⅔=3⅓
3⅓=3⅓

o)
0,3x - 2(0,1x +1)=0
0,3x-0,2x-2=0
0,3x-0,2x=2
0,1x=2
x=20

spr:
0,3*20-0,2*20-2=0
6-4-2=0
0=0

p)
0,5(x-3) + 0,25(2x +6)=5
0,5x-1,5+0,5x+1,5=5
0,5x+0,5x=5+1,5-1,5
x=5

spr:
0,5*5-1,5+0,5*5+1,5=5
2,5-1,5+2,5+1,5=5
5=5
1 5 1